Effect of repeated caffeine ingestion on repeated exhaustive exercise endurance - Bell, D. G.; McLellan, T. M. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this study was to examine the effect of repeated doses of caffeine on repeated exercise endurance. METHODS Nine male caffeine users performed exercise rides (ER) to exhaustion at 80% VO(2max) after ingesting a placebo, 5 mg x kg-1 of caffeine, or 2.5 mg x kg-1 of caffeine 1 h before the ER. Two ER were performed weekly on the same day once in the morning (AM) and 5 h later in the afternoon (PM). There were four treatments containing either caffeine or placebo, i.e., trial A representing 5-mg x kg-1 caffeine in the AM and 2.5-mg x kg-1 caffeine in the PM; trial B, which was placebo in both AM and PM; trial C representing 5-mg x kg-1 caffeine in the AM and placebo in the PM; and trial D representing a placebo in the AM and 5-mg x kg-1 caffeine in the PM. The order of the treatment trials was double blind and randomized. RESULTS: Caffeine ingestion significantly increased exercise time to exhaustion in the AM (trial A 24.9 +/- 10.2 min and trial C 21.8 +/- 4.9 vs trial B 18.0 +/- 6.4 min and D 17.7 +/- 4.3 min). This effect was maintained in the PM and greater than placebo (B 18.3 +/- 4.8 min) regardless of whether redosing (trial A 21.5 +/- 8.6 min) or placebo (trial C 21.0 +/- 6.8) followed the initial morning dose. Caffeine dosing in the PM (trial D 22.4 +/- 7.2 min) also increased ER after placebo trial D in the AM. CONCLUSIONS: It was concluded that redosing with caffeine after exhaustive exercise in the AM was not necessary to maintain the ergogenic effect of the drug during subsequent exercise 6 h later.